Environmental Performance, Corporate Governance and Financial Performance of Chinese Heavy Polluted Industries - Anqi, Chen; San, Ong Tze (International Journal of Energy Economics and Policy, 2022)
Heavy polluted industries are the primary source of environmental pollution. In the case of the decline of ecological carrying capacity, how to ensure the necessary protection of the environment and the development of financial benefits, and whether corporate governance can regulate environmental performance and financial performance will be explored. This paper uses IBM SPSS Statistics 26.0 to conduct factor analysis to process dimensionality reduction on aggregate environmental performance based on statistics from heavy polluted industry companies listed on Shenzhen and Shanghai stock markets from 2015 to 2019. Then stata16.0 was used for regression analysis. It is found that a company’s aggregate environmental performance has a beneficial influence on its financial performance. Financial performance is also influenced by the size of the company and the rate at which revenues rise. Furthermore, the ratio of female board members has a beneficial effect on the link between a company’s aggregate environmental and financial performance, and the total number of committees has a strong negative impact on the relation between aggregate environmental and financial performance. These findings back up the agency, stakeholder, and resource-based theories, and they have significant consequences for the company’s management, legislators, and regulators.